Genetically Determined Inflammatory Biomarkers and the Risk of Heart Failure: A Mendelian Randomization Study - Li, Xintao; Peng, Shi; Guan, Bo; Chen, Songwen; Zhou, Genqing; Wei, Yong; Gong, Chao; Xu, Juan; Lu, Xiaofeng; Zhang, Xiaoyu; Liu, Shaowen (Frontiers in Cardiovascular Medicine, 2021)
Background: Positive associations between inflammatory biomarkers and the risk of heart failure (HF) have been reported in conventional observational studies. However, the causal effects of inflammatory biomarkers on HF have not been fully elucidated. We conducted a Mendelian randomization (MR) study to examine the possible etiological roles of inflammatory biomarkers in HF. Methods: Summary statistical data for the associations between single nucleotide polymorphisms (SNPs) and C-reactive protein (CRP), fibrinogen, and components of the interleukin-1 (IL-1)-interleukin-6 (IL-6) inflammatory signaling pathway, including interleukin-1β (IL-1β), IL-1 receptor antagonist (IL-1ra), IL-6, and soluble IL-6 receptor (sIL-6r), were obtained from genome-wide association studies (GWAS) for individuals of European descent. The GWAS dataset of 977,323 participants of European ancestry, including 47,309 HF cases and 930,014 controls, was collected to identify genetic variants underlying HF. A two-sample Mendelian randomization framework was implemented to examine the causality of the association between these inflammatory biomarkers and HF. Results: Our MR analyses found that genetically determined CRP and fibrinogen were not causally associated with HF risk (odds ratio [OR] = 0.93, 95% confidence interval [CI] = 0.84-1.02, p = 0.15; OR = 0.94, 95% CI = 0.55-1.58, p = 0.80, respectively). These findings remained consistent using different Mendelian randomization methods and in sensitivity analyses. For the IL-1-IL-6 pathway, causal estimates for IL-6 (OR = 0.86, 95% CI 0.81-0.91, p < 0.001), but not those for IL-1β, IL-1ra, or sIL-6r, were significant. However, the association between genetically determined IL-6 and HF risk became nonsignificant after excluding SNPs with potential pleiotropy (OR = 0.89, 95% CI = 0.77-1.03, p = 0.12). Conclusion: Our study did not identify convincing evidence to support that CRP and fibrinogen, together with their upstream IL-1-IL-6 signaling pathway, were causally associated with heart failure risk.